Design of Two Optimized Controllers of a Hydraulic Actuator Semi-Active Suspension: A Comparison Study - Babesse, S. (Engineering, Technology & Applied Science Research, 2019)
A parallel optimization of Proportional, Integral and Derivative (PID) controller and a sixth order phase lead-lag compensator of a high order naturally oscillatory hydraulic actuator are proposed in this paper. The PID controller parameters (proportional, integral and derivative) and the compensator parameters (gain, poles and zeros) are obtained by minimizing the Integral of Time Absolute Error (ITAE) criterion. The proposed methods are demonstrated through a realistic numerical synthesis example of a hydraulic actuator dedicated to a semi-active suspension modeled by an eighth order transfer function. A simulation comparison is investigated for both controllers to compare their performances.